(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
This study aims to address the topic of which techniques have shown to be the most successful in enhancing clinical nursing documentation in the acute hospital environment. A search using keywords was performed in the CINAHL and Medline databases to find relevant papers. The studies were assessed for their level of evidence based on the standards of the GRADE framework. The data obtained from each trial were included into a Summary of Dataset (SOD) spreadsheet. For each trial, if available, we estimated the percentage compliance scores before and after the intervention. This was done by dividing the mean score by the potential total score and multiplying it by 100. The proportion of the improvement in adherence for each trial was determined by reducing the pre-intervention value from the post-intervention value. The compliance score modification and the post-intervention compliance score were included in the SOD and used for comparative analysis amongst the trials. The intervention techniques adopted in each research were evaluated thematically. The study evaluated compliance rates and interventions to assess the effectiveness of different tactics in producing a significant increase in compliance. Several research used documentation audits along with personalized comments as a strategy to enhance nursing documentation. Ten of these trials had a compliance rate of 70% or higher after the intervention. Despite the limits of this research, it is possible that conducting a record-keeping inspection with personal input, together with additional context-specific tactics, may be a dependable approach for achieving substantial enhancements in clinical nursing record. The current level of proof is deemed to be very insufficient, necessitating the need for more study.